11th International Conference on Permafrost: exploring permafrost in a future earth : book of abstract : 20-24 June 2016, Postdam, Germany - Morgenstern, Anne; Günther, Frank (Bibliothek Wissenschaftspark Albert Einstein, 2016)
Preface The Local Organizing Committee (LOC) of the Eleventh International Conference on Permafrost (ICOP2016) is excited about the breadth and the quality of the abstracts submitted for this conference. It was the first time that ICOP topical sessions were not set by the organizing committee in a top-down manner. Instead, sessions were submitted from the bottom-up by groups of researchers and engineers from all over the world. This grassroots effort prompted the submission of many innovative topics covering the full range of modern permafrost research. It also facilitated not only the engagement of the core permafrost community, but also of science disciplines traditionally less involved in ICOPs. In total, 51 session proposals were received by the LOC. These were submitted by up to three conveners including at least one early career researcher from the Permafrost Young Researchers Network (PYRN). After the evaluation process by the International Scientific Committee (ISC) and the LOC, including the addition of strategic topics and the combination of sessions with thematic overlap, 40 topical sessions were eventually opened for abstract submission. There was yet another novelty compared to previous ICOPs: the submission of contributions was not divided into abstracts and papers, in favor of a quicker and uniform review process allowing for the submission deadline to be set closer to the conference. This opened the possibility for authors to present recent results in the rapidly evolving field of permafrost research. Abstracts of up to 3000 words were allowed, either plain or formatted with subheadings, and including one figure, table or equation. We received the extraordinary number of 980 abstracts. This number varied between 79 and 0 among sessions, which led to a further consolidation into the final set of 32 sessions presented in this abstract volume. Abstract evaluation was placed in the hands of the session conveners. The vast majority of abstracts (97 %) was deemed eligible to be accepted for presentation during the conference, either immediately or after revision by the authors. The reduced number of abstracts presented in this volume is mostly due to the inability of travelling to the conference for some authors. We are very delighted that the modified procedures for the compilation of the scientific conference program proved so successful and wish to extend our gratitude to the session conveners and ISC members for their tremendous efforts and great support in compiling such a high-quality program. We also wish to thank Hans-Wolfgang Hubberten, Lydia Polakowski, Matthias Fuchs, Ingmar Nitze, Samuel Stettner, Karina Schollaen, Hugues Lantuit, and Guido Grosse for their technical help in the final editing phase of this abstract volume. Frank Günther and Anne Morgenstern
Datenlieferant: Alfred Wegener Institute for Polar- and Marine Research (AWI): ePIC (electronic Publication Information Center)
Nasl. z nasl. zaslona
Opis vira z dne 23. 10. 2022
Keywords: Konferenzschrift